Perspectives of herbs and their natural compounds, and herb formulas on treating diverse diseases through regulating complicated JAK/STAT signaling - Chen, Jian-Yu; Xiao-Yun Tian,; Wei, Shan-Shan; Yang, Ying-Jie; Deng, Shan; Jiao, Chun-Jie; Wang, Can-Jian; Chu, Ke-Dan; Ma, Xue-Qin; Xu, Wei (Frontiers in Pharmacology, 2022)
JAK/STAT signaling pathways are closely associated with multiple biological processes involved in cell proliferation, apoptosis, inflammation, differentiation, immune response, and epigenetics. Abnormal activation of the STAT pathway can contribute to disease progressions of various conditions. Besides, tofacitinib and baricitinib as the JAK/STAT inhibitors have been recently approved by FDA for rheumatology disease treatment. Therefore, influences on the STAT signaling pathway have the potential and perspective approaches for diverse diseases. Chinese herbs in Traditional Chinese Medicines (TCM), which are widespread throughout China, are the gold resources of China and have been extensively used for treating multiple diseases for thousands of years. However, Chinese herbs and herb formulas are characterized by complicated components, resulting in various targets and pathways in treating diseases, which limits their approval and applications. With the development of chemistry and pharmacology, active ingredients of TCM and herbs and underlying mechanisms have been further identified and confirmed by pharmacists and chemists, which improved, to some extent, awkward limitations approval and applications regarding TCM and herbs. In this review, we summarized various herbs, herb formulas, natural compounds, and phytochemicals isolated from herbs that have the potential for regulating multiple biological processes via modulation of the JAK/STAT signaling pathway based on the published work. Our study will provide support for revealing TCM, their active compounds treat diseases, and the underlying mechanism, which further improving TCM spread rapidly to the world.